Impact Of Work From Home (Wfh) On Productivity And Job Satisfaction Of It Sector Employees - Rana, Shivati; Aggarwal, Nidhi; Bhatia, S (Journal of Neonatal Surgery, 2025)
In the highly developed and internationalized world of today, couples with more education have access to better job prospects, high incomes, and first-rate services. The roles and responsibilities within the family are constantly shifting as more and more Working couples were pursuing their professional objectives by participating in the productive workforce. People's expectations for success and reaching their personal and professional goals have grown significantly. The COVID-19 epidemic has had a global influence on all industries, and as a result, works from home policies have been embraced. In COVID-19, having a professional job has become both mandatory and important for couples. Working couples have faced various possibilities and problems in juggling their career aspirations with family duties.